Foundations of dialogue between the philosophy of limit and the philosophy of nothingness: Eugenio Trías and the Kyoto School - Segade Alonso, Carlos E. (Pensamiento. Revista de Investigación e Información Filosófica, 2022)
The philosophy of nothingness was Kitaro Nishida’s answer to the necessity of laying the foundations of a philosophical dialogue with the West. This paper suggests that this dialogue, which the Kyoto School still continues, might accept Eugenio Trías’ philosophy of limit as one of their Western references. To do so, and after reviewing the main concepts of each philosophical proposal, Trías’ categorical analysis of history will be studied along with the founding concepts of «nothingness» and «limit», which represent the background for humanist ethics open to dialogue with both cultures.
Keywords: philosophy of limit; philosophy of nothingness; Kyoto School; spirit; emptiness